2018
DOI: 10.3390/e20100770
|View full text |Cite
|
Sign up to set email alerts
|

Operating Range for a Combined, Building-Scale Liquid Air Energy Storage and Expansion System: Energy and Exergy Analysis

Abstract: This paper presents the results of an ideal theoretical energy and exergy analysis for a combined, building scale Liquid Air Energy Storage (LAES) and expansion turbine system. This work identifies the upper bounds of energy and exergy efficiency for the combined LAES-expansion system which has not been investigated. The system uses the simple Linde-Hampson and pre-cooled Linde-Hampson cycles for the liquefaction subsystem and direct expansion method, with and without heating above ambient temperature, for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Such cycle is not commercially viable and is used on a very narrow scale because of several limitations including poor liquid yield, very high pressures, low exergy efficiency, and cycle irreversibility. 55 Therefore, the research carried out on this cycle is limited and further work has been carried out on Claude and Kapitza cycles.…”
Section: Air Liquefaction Systemmentioning
confidence: 99%
“…Such cycle is not commercially viable and is used on a very narrow scale because of several limitations including poor liquid yield, very high pressures, low exergy efficiency, and cycle irreversibility. 55 Therefore, the research carried out on this cycle is limited and further work has been carried out on Claude and Kapitza cycles.…”
Section: Air Liquefaction Systemmentioning
confidence: 99%
“…Table-III shows these findings. Computer aided thermodynamic tables are used to get enthalpy and entropy values, from pressure and temperature data, in turn to calculate exergy and efficiency [5], [10].…”
Section: …(6)mentioning
confidence: 99%
“…Their study concluded that such a configuration can achieve an overall RTE between 52% and 76%. A LAES-assisted polygeneration system for micro-grids applications has also been proposed by Mazzoni et al [14], Howe et al [15] focused on a combined, building-scale LAES and expansion system, while Szablowski et al [16] analysed exergetically an adiabatic LAES system using the Linde-Hampson liquefaction cycle.…”
Section: Introductionmentioning
confidence: 99%